Efektifitas Gerakan Vertical Jump Terhadap Daya Ledak Atlet SSB Kancil Mas Karawang - Mochamad Qesha Arief Arief; Deden Akbar Izzuddin; Habibi Hadi Wijaya (Indonesian Journal of Kinanthropology (IJOK), 2024)
Background: This study aims to evaluate the effectiveness of the vertical jump movement in increasing explosive power in Kancil Mas Karawang Football School (SSB) football athletes. Methods: This research was carried out by collecting data from a number of athletes who had undergone vertical jump training regularly over a certain period. The experimental method was used in this research, where participants were divided into a control group and an experimental group. The experimental group underwent vertical jump training, while the control group did not experience additional training intervention. Explosive power measurements were carried out before and after the intervention period using standard tests whose reliability has been proven. Results: The results of data analysis showed a significant increase in explosive power in the experimental group compared to the control group. The implications of these findings for athletic training, especially in the context of explosive power development in soccer, are discussed in this study. Conclusions: . In conclusion, vertical jump training can be an effective method in increasing the explosive power of soccer athletes at SSB level, with the potential to improve athlete performance on the field.